2018
DOI: 10.37275/ijr.v8i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Validity And Reliability Of Lupus Quality Of Life Questionnaire In Patients With Systemic Lupus Erythematosus In Indonesia

Abstract: Background: The development of Systemic Lupus Erythematosus (SLE) treatment has led the increased of patients survival. Quality of life has became a value based medicine component that should be evaluated in treating SLE. One standardized questionnaire to asses the quality of life in SLE patients is Lupus Quality of Life (Lupus QoL). Currently, in Indonesia, there has not been any spesific questionnaire to asses the quality of life in SLE patients. This study aims to prove that Lupus QoL is valid and reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…4 44 In the original derivation of LupusQoL, although only women of two racial ethnicities were involved, white and South Indians, subsequent validations included a wider population as well as men. 4 Reliability (internal consistency and test-retest) Internal consistency of LupusQoL domains was assessed in three studies [44][45][46] and Cronbach's α ranged from 0.85 to 0.94 across studies and domains (online supplementary table S7). Assessment of the test-retest reliability of LupusQoL indicated intraclass correlations (ICCs) ranging from 0.68 to 0.95 (online supplementary table S7), 4 45 46 (table 3).…”
Section: Content Validitymentioning
confidence: 99%
“…4 44 In the original derivation of LupusQoL, although only women of two racial ethnicities were involved, white and South Indians, subsequent validations included a wider population as well as men. 4 Reliability (internal consistency and test-retest) Internal consistency of LupusQoL domains was assessed in three studies [44][45][46] and Cronbach's α ranged from 0.85 to 0.94 across studies and domains (online supplementary table S7). Assessment of the test-retest reliability of LupusQoL indicated intraclass correlations (ICCs) ranging from 0.68 to 0.95 (online supplementary table S7), 4 45 46 (table 3).…”
Section: Content Validitymentioning
confidence: 99%
“…3 Research showed that the quality of life of SLE patients decreased compared to the general population. 4 In addition, the quality of life of patients with SLE was lower than other chronic diseases, 5 both in physical and mental dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…This study also has some limitations. Validity and reliability tests for other quality of life instrument did not just only analyze the validity by referring to its Pearson's r value, but also did other validity tests such as convergent and discriminant validity, known-groups validity, and also factor analysis [6][7][8][12][13][14]. Further validity and reliability test in other groups is also needed.…”
Section: Discussionmentioning
confidence: 99%